Semeadura direta para restauração de floresta tropical: efeitos de arranjos de espécies no estabelecimento e crescimento inicial da comunidade arbórea - Horle, Daniel Carlos (2021)
Direct seeding is a common technique for tropical forest restoration, however we lack detailed knowledge on species arrangements, overall implementation and optimal costs to allow its more efficient large-scale use. We evaluated whether direct seeding through different species arrangements affected the early-establishment of the community and of some of tree species. We tested four seeding richness arrangements (seven, 13, 21 and 29 species), sowing the same density for all treatments, altering density per species. In a site destined for the Brazilian Seasonal Atlantic Forest restoration, we installed 24 plots of 10 m × 3 m each, in a randomized design. We counted and measured seedling height and stem diameter and estimated the costs for seed purchase, implementation, and maintenance of each treatment up to one year after sowing. Richness variation among treatments were reduced after sowing, since many species did not emerge. Thus, we evaluated the effect of different sowing densities on the five species that emerged in all arrangements. The treatment with less species had higher seedling density, but basal area, mean seedling diameter and height of seedlings in the community did not varied among treatments. Species did not change establishment rate nor growth according to sowing density. Cost per seedling was higher in the richest arrangement, however it varied only 8.5% among treatments and similar to the cost of tree seedlings plantings. Prioritizing species with high establishment rate may reduce the costs of direct seeding, however it may not be as cheap as previously reported in other initiatives.